Multiparticulate drug delivery : formulation, processing and manufacturing - Rajabi-Siahboomi, Ali R. (Springer, 2017)
Authored by leading experts from academia, users and manufacturers, this book provides an authoritative account of the science and technology involved in multiparticulate drug delivery systems which offer superior clinical and technical advantages over many other specialized approaches in drug delivery. The book will cover market trends, potential benefits and formulation challenges for various types of multiparticulate systems. Drug solubility, dose, chemistry and therapeutic indications as well as excipient suitability coupled with manufacturing methods will be fully covered. Key approaches for taste-masking, delayed release and extended release of multiparticulates systems are of significant interest, especially their in-vivo and in-vitro performance. In addition, the principles of scale-up, QbD, and regulatory aspects of common materials used in this technology will be explained, as well as recent advances in materials and equipment enabling robust, flexible and cost-effective manufacture. Case studies illustrating best practices will also make the book a valuable resource to pharmaceutical scientists in industry and academia.- Resumé vydavatel
Chapter 6: Science and Practice of Microencapsulation Technology.
Keywords: dávkování léků; léky; farmakologie; drug dosage calculations; drugs; pharmacology; elektronické knihy; sborníky; electronic books; papers of several authors